The computational methods and application comparisons for the interaction between surrounding rock and lining in hydraulic tunnels - Yin, Chonglin; Xia, Yong; Zhu, Zhende; Xie, Jinyuan; Tang, Bihua; Luo, Chun (Frontiers in Earth Science, 2025)
Hydraulic tunnels are subjected to both internal and external water pressures, which further complicates the contact behavior between the surrounding rock and the lining. Currently, analyses addressing this issue remain insufficiently thorough, and this phenomenon is particularly prominent in engineering applications. For this purpose, this study established a unified analytical framework, integrating adhesive, smooth and frictional slip contact, then compared and analyzed the interaction mechanism between the surrounding rock and the lining using numerical and analytical methods. The research results show that a critical friction threshold governs contact behavior, below which interfacial slip reduces lining tensile stress by 9.5% through stress redistribution; Elastic modulus ratio E2/E1 dominates stress sensitivity, an increase from 2 to 5 elevates crown tension by 80.3%—far exceeding thickness effects; The lateral pressure coefficient and the displacement release coefficient have significant impacts on both the distribution pattern and the magnitude of stresses. Appropriately delaying the timing of lining installation can effectively reduce the stresses in the lining. The new variable reduction algorithm proposed in this paper accelerates computation by 75% and improves accuracy by 2.2%, which is highly feasible. This mechanics-based framework transforms lining design from empirical practice to quantified optimization, delivering actionable protocols for the safety and economy of hydropower infrastructure.